Peace operations seen from below : UN missions and local people - Pouligny, Beatrice (Kumarian Press, 2006)
"Cambodia, Somalia, Mozambique, Bosnia, Haiti, Sierra Leone - all have been the subject of interventions by armed UN units sent to stabilize societies riven by political and ethnic antagonism." "Apart from anecdotal reportage, little is known or has been investigated about how local inhabitants in these and other cities interact with and respond to peacekeepers in their midst. Most studies of post-conflict situations focus on political elites, the demobilization of armed groups and the question of whether externally determined criteria for state reconstruction have been met."